The Motivation Students of Universitas PGRI Palembang in Participating of Sports Achievement Training Performance Activities (KOP) Volleyball Cup - Oktaria, Wiwik; Manullang, Jujur Gunawan; Junaidi, Ilham Arvan (Journal of Social Work and Science Education, 2023)
This research has the aims to make an article entitled Motivation of Palembang PGRI University Students in Participating in Volleyball Cup Training discusses the development of achievement sports activities (KOP) which have participated in many student-level competition activities throughout South Sumatra and have won many championship ratings in each game. This was proven at the South Sumatra Regional Student Sports Week (POMDA) 2022 where the men’s volleyball KOP team from Palembang PGRI University won 2nd place, while the women’s team won 3rd place in the event. The population and sample in this study were students who took part in volleyball training at PGRI Palembang University, totaling 20 boys and 10 girls with a total of 30 people. By using quantitative descriptive research methods. Meanwhile, data and data sources are divided into two, namely primary data and secondary data. Data collection techniques in this study used questionnaire. For the indicators of measuring the variable grids in questionnaires with the test Validation and Reliability Questionnaire. Through the above data collection, not all members in the group have good competency skills, especially in increasing their motivation to rise. Sometimes they have difficulty in increasing motivation among their peers. And they believe that correction from their peer’s correction of their peers fairly, increasing motivation towards achievement in every competition. And the result of all indicators shows that both internal and external factors give significant contributions toward achievement.